Fabrication of transparent and photoluminescent poly(vinyl butyral)/carbon dots nanocomposite thin film. (10th February 2015) - Fu, Xiaobo; Yu, Yong; Feng, Jiyun; Ming Ng, Ka
Abstract: To develop better functional nanomaterials, photoluminescent (PL) transparent poly(vinyl butyral) (PVB) nanocomposite thin films containing carbon dots (CDs) were fabricated by a simple solution blending method. The PL CDs with mean diameters of about 5 nm were synthesized by a chemical oxidation method and were then characterized by UV–vis, PL and XPS techniques. The CDs solution was blended with PVB solution under ultrasonication followed by evaporation of solvent ethanol, forming PVB/CDs nanocomposite thin films. Both CDs and PVB/CDs nanocomposite thin films show light dependent absorption properties. As compared to the only fluorescent emission peak at 600 nm of CDs, the PVB/CDs nanocomposites thin films show an excitation wavelength dependent fluorescent emission property and the PL intensity of the PVB/CDs nanocomposites thin films were strongly enhanced. It was found that the surface functional groups (defect sites) of the CDs were responsible for the strong PL properties. In addition, no photo bleach of the PVB/CDs nanocomposite thin film under UV light (330–385 nm) was observed, indicating that the PL properties of the nanocomposite thin films were very stable.